GRIEVING: PROBLEMS AND EFFORTS TO ADDRESS IT FROM A SOCIAL WORK PERSPECTIVE Systematic Literature Review (SLR) - Meiti Subardhini; Kanya Eka Santi; Rini Hartini Rinda; Sakroni (Adisam Publisher, 2026)
Grieving is a human response to loss, whether the loss results from death or from non-death losses such as the loss of health, employment, social roles, relationships, bodily functions, a sense of safety, and life expectations. In social work practice, grieving should not be understood merely as a sequence of emotional stages, but as a biopsychosocial-spiritual adaptation process shaped by the meaning of loss, social support, culture, spirituality, access to services, and structural vulnerability. This article aims to strengthen understanding of grieving-related problems and strategies for addressing them through a PRISMA-based systematic literature review (SLR). The literature reviewed was limited to publications from 2023 onward, with priority given to reputable articles on prolonged grief disorder (PGD), risks of prolonged grief, psychosocial interventions, family- and community-based support, digital bereavement support, and caregiver and palliative care contexts. The synthesis identified five main themes: first, the shift in the concept of grief from a stage model toward a dynamic adaptation model; second, PGD as a clinical condition that differs from normal grief, depression, and PTSD; third, risk factors that include pre-loss grief, depression, traumatic death, strong attachment, loneliness, low social support, and cultural barriers; fourth, the effectiveness of interventions that combine psychoeducation, narrative reconstruction, cognitive-behavioral therapy, exposure, social support, EMDR, mindfulness, and online support; and fifth, the importance of the social worker's role in assessment, emotional validation, resource advocacy, crisis intervention, clinical referral, and strengthening social functioning. The discussion emphasizes that the purpose of intervention is not to erase grief, but to help individuals and families integrate loss into a meaningful life narrative. Recommendations are directed toward the development of tiered service models, PGD screening instruments, strengthened community support, social worker training, and Indonesian research grounded in culture and spirituality.